BUMDesa Development of BUMDesa to Increase The Economic Resilience of The Community in Au Wula Village - Angge, Kandidatus; Pardiman, Pardiman; Farida, Eka (LPPM of NAROTAMA UNIVERSITY, 2023)
Purpose: This study aims to find out and analyze the application of management, collaboration with other parties, and local economic development of BUMDesa to increase the economic resilience of the community in Au Wula village. Methodology: The research design is a research-based development. The development design is based on the model of increasing community economic resilience through BUMDesa management practices and the PIID-PEL program approach. The stages of the research consisted of pre-field, implementation, data analysis, data presentation, drawing conclusions, and checking the validity of the data. Findings: The results showed that the increase in the economic resilience of the Au Wula village community was the result of the development and implementation of: (1) General management elements at BUMDesa include planning, organizing, directing, coordinating and controlling; (2) Collaborative management with 60 farmers, adding manpower, synergizing transportation, opening a vegetable market, and scholarship programs from elementary schools to master's programs; (3) Development of the local economy through the establishment of ecotourism centers, MSME centers, and the involvement of youth groups. Implications: Development and application of general management, collaborative management, and local economic development at BUMDesa can be used to grow and increase economic resilience in villages. Practical implications: Implementation of management governance, collaboration, and local economic development in the village. Originality/value: The application of governance includes management, collaboration, and local economic development will grow and increase village economic resilience. Paper type: Research paper